Biology, natural history and temporal fluctuation of the geometrid Oospila pallidaria associated with host plant phenology. (3rd May 2016) - de Sousa-Lopes, Bruno; Bächtold, Alexandra; Del-Claro, Kleber
ABSTRACT: We investigated the temporal fluctuation of the geometrid moth Oospila pallidaria and related it to the leaf flush season of its host plant, Mimosa setosa, and to environmental factors. Aspects of the natural history of adults are also described. Mimosa setosa produced leaves all year round, but abundance of O. pallidaria larvae in the field was seasonal. The abundance of immatures showed a tendency to decrease with rainfall and temperature. Our study is pioneering in that it provides insights into factors related to the occurrence of O. pallidaria in natural areas. In addition, the biology of immatures is provided.